Inovasi Building Automation System (BAS) pada Desain Kedai Kopi Islami di Aceh Besar - Ardhian, Raudhatul Athfal; Andari, Wenni; Jaraputra, REza Maulana Geubrina Effendy (Universitas Medan Area, 2025)
The development of globalization has encouraged the use of technology as a key element in facilitating access to information, social interaction, and expanding business connectivity. Technology has now become a secondary need that supports primary needs, including the application of smart systems such as building automation systems (BAS) for managing devices from inside and outside buildings. Additionally, sustainable innovations such as rainwater harvesting, biopores, grass blocks, and two-sided glass fountain technology also contribute to optimizing natural potential in landscape design. This journal aims to design a coffee shop in an Islamic-regulated area using an architectural approach aligned with Islamic values, principles, and guidelines, while integrating BAS as a form of technological innovation. This study employs a phenomenological research method with a descriptive qualitative approach, using ground research for data collection. The application of Islamic values in architecture and landscape design also includes the separation of zones between men and women, as an effort to preserve Aceh's identity, which upholds Islamic sharia law.